2015
DOI: 10.1186/s12875-015-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain syndromes are associated with high rates of recidivism and costs in young United States Veterans

Abstract: BackgroundRecurrent chest pain is common in patients with and without coronary artery disease. The prevalence and burden of these symptoms on healthcare is unknown.ObjectivesTo compare chest pain return visits (recidivism) in patients with unexplained chest pain (UCP) against reference group of patients with coronary artery disease (CAD) and estimate the annual cost of recurrent chest pain.MethodsIn a retrospective cohort study, a Veteran Affairs (VA) administrative and clinical database of Veterans who were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…First, our findings suggest that CMD could account for many cases of unexplained chest pain, which have been linked to recurrent symptoms, high rates of return visits and poor functional outcomes in both the ED and outpatient settings. 21,22 Similar to observed rates of CMD in higher-risk cohorts (21-63%), 6,23-25 we found a surprisingly high rate of CMD in low to moderate risk patients (42%). We also found that one third of patients with CMD reported prior episodes of chest pain, many of whom sought ED care but were discharged home with a diagnosis of unexplained chest pain.…”
Section: Discussionsupporting
confidence: 87%
“…First, our findings suggest that CMD could account for many cases of unexplained chest pain, which have been linked to recurrent symptoms, high rates of return visits and poor functional outcomes in both the ED and outpatient settings. 21,22 Similar to observed rates of CMD in higher-risk cohorts (21-63%), 6,23-25 we found a surprisingly high rate of CMD in low to moderate risk patients (42%). We also found that one third of patients with CMD reported prior episodes of chest pain, many of whom sought ED care but were discharged home with a diagnosis of unexplained chest pain.…”
Section: Discussionsupporting
confidence: 87%
“…Chest pain is one of the most common presenting complaints in outpatient visits and to the emergency department [47,48]. Of the patients who are referred for coronary angiography, with or without ischemia on non-invasive stress testing, 20–50% are found to have angiographically normal coronary arteries [3,49,50].…”
Section: Assessment Of Microvascular Disease and Endothelial Dysfumentioning
confidence: 99%
“…Of the patients who are referred for coronary angiography, with or without ischemia on non-invasive stress testing, 20–50% are found to have angiographically normal coronary arteries [3,49,50]. Despite the absence of epicardial coronary artery disease by angiography many patients suffer recurrent presentations for chest pain [48,50]. There is increasing awareness of pathologies beyond obstructive coronary stenosis that can cause myocardial ischemia, including diffuse epicardial coronary artery disease, occlusion of small secondary branches, microvascular disease, or low baseline resting flow [51,52].…”
Section: Assessment Of Microvascular Disease and Endothelial Dysfumentioning
confidence: 99%
“…7 It is also associated with persistent chest pain, repeat health services utilization, and poor patient function, with disease-related costs that mount to $13 billion. [10][11][12] Thus, early diagnosis and optimal management of symptomatic CMD is critical.…”
Section: Introductionmentioning
confidence: 99%